2016
DOI: 10.24123/aipj.v31i2.568
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profile Differences Between Prisoners and Non-Prisoners Using the Personality Inventory for DSM-5 (PID-5)

Abstract: Prison provides correctional function for prisoners. There are some factors needed to be considered to enable the correctional process work optimally, one of them is the personality of prisoners. We need to consider this because there are different kinds of prisoners with different criminal backgrounds. This study aimed to identify the personality profiles of prisoners, including violent offenders, non-violent offenders and drug offenders, using the Indonesian version of Personality Inventory for DSM-5 (PID-5)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 11 publications
0
1
1
Order By: Relevance
“…In contrast with previous evidence [ 36 ], we did not detect a role of suspiciousness, cognitive and perceptual dysregulation, grandiosity, and a lack of eccentricity as predictors of sex crime. An explanation for this result might be the fact that in our statistical model we controlled for the effect of psychiatric comorbidity which had not been controlled for in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast with previous evidence [ 36 ], we did not detect a role of suspiciousness, cognitive and perceptual dysregulation, grandiosity, and a lack of eccentricity as predictors of sex crime. An explanation for this result might be the fact that in our statistical model we controlled for the effect of psychiatric comorbidity which had not been controlled for in previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Adhiatma and Halim [ 36 ] found that as compared with a non-prisoner group, prisoners who had committed crime against the person had higher levels on a number of facets including Hostility, Depressivity, Suspiciousness, Callousness, Withdrawal, Intimacy Avoidance, Anhedonia, Restricted Affectivity, Irresponsibility, Impulsiveness, Unusual Beliefs and Experiences, and Perceptual Dysregulation. In addition, as compared with a non-prisoner group, prisoners who had committed property crime had higher Depressivity, Suspiciousness, Callousness, Withdrawal, Intimacy Avoidance, Anhedonia, Restricted Affectivity, Unusual Beliefs and Experiences, and Perceptual Dysregulation [ 36 ]. In a more recent study using the PID-5, Russell and King [ 31 ] found that Suspiciousness, Cognitive and Perceptual Dysregulation, Grandiosity, and lack of Eccentricity emerged as predictors of sexual violence.…”
Section: Introductionmentioning
confidence: 99%